2004
DOI: 10.1002/jbm.a.30083
|View full text |Cite
|
Sign up to set email alerts
|

Poly(anhydride‐ester) fibers: Role of copolymer composition on hydrolytic degradation and mechanical properties

Abstract: Poly(anhydride-esters), based on carboxyphenoxydecanoate (CPD), are biocompatible polymers that hydrolytically degrade. The mechanical properties of the poly(anhydride-esters) can be altered by copolymerization with para-carboxyphenoxyhexane (pCPH). Mechanical properties of three CPD:pCPH compositions (30:70, 40:60, and 50:50) are reported as a function of hydrolytic degradation. The mechanical characteristics evaluated were tensile modulus at 1% strain (E(1%)), tensile strength (sigma(B)), ultimate elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 80 publications
(102 reference statements)
0
43
0
Order By: Relevance
“…Chemical copolymerization of SA-based (sebacic) PAE and para-carboxyphenoxyhexane (pCPH) repeat units (Figure 13) yielded a copolymer with significantly higher T g compared to the SA-based homopolymer (33 °C versus 27 °C), which greatly enhanced its processability at room temperature. 92 In addition, different ratios between the SA-based (sebacic) PAE and pCPH units resulted in different copolymer properties: higher pCPH percentage yielded copolymers with lower tensile strength, lower Young’s modulus, lower ultimate elongation and lower toughness as the pCPH unit is more brittle than the SA-based unit. 92 Copolymers with more pCPH units were also more hydrophobic, which led to a slower hydrolytic degradation rate and, thus, less significant changes in polymer properties when incubated in PBS.…”
Section: Tunability and Manipulations Of Paesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical copolymerization of SA-based (sebacic) PAE and para-carboxyphenoxyhexane (pCPH) repeat units (Figure 13) yielded a copolymer with significantly higher T g compared to the SA-based homopolymer (33 °C versus 27 °C), which greatly enhanced its processability at room temperature. 92 In addition, different ratios between the SA-based (sebacic) PAE and pCPH units resulted in different copolymer properties: higher pCPH percentage yielded copolymers with lower tensile strength, lower Young’s modulus, lower ultimate elongation and lower toughness as the pCPH unit is more brittle than the SA-based unit. 92 Copolymers with more pCPH units were also more hydrophobic, which led to a slower hydrolytic degradation rate and, thus, less significant changes in polymer properties when incubated in PBS.…”
Section: Tunability and Manipulations Of Paesmentioning
confidence: 99%
“…92 In addition, different ratios between the SA-based (sebacic) PAE and pCPH units resulted in different copolymer properties: higher pCPH percentage yielded copolymers with lower tensile strength, lower Young’s modulus, lower ultimate elongation and lower toughness as the pCPH unit is more brittle than the SA-based unit. 92 Copolymers with more pCPH units were also more hydrophobic, which led to a slower hydrolytic degradation rate and, thus, less significant changes in polymer properties when incubated in PBS. 92 These parameters are important for choosing bioactive-releasing implant materials with stable properties after implantation.…”
Section: Tunability and Manipulations Of Paesmentioning
confidence: 99%
“…HME was used to prepare PolyAspirin TM , which is a fiber composed of a poly(anhydride-ester) synthesized by copolymerization of salicylate monomer, carboxypenoxydecanoate (CPD) and para-carboxyphenoxyhexane (pCPH). In an aqueous environment, PolyAspirin TM undergoes hydrolysis, which results in the formation and release of salicylic acid [51].…”
Section: Polyanhydridesmentioning
confidence: 99%
“…A previous study showed that SAPAE polymer pliability and SA release can be changed by copolymerization of different SAPAE monomers. 60 In this study, PCL was electrospun with the FD-SAPAE or the SD-SAPAE polymer to improve the handling characteristics of the electrospun membrane. Composite membranes containing 60% PCL and 40% SAPAE were found to have optimal handling characteristics, which included sufficient pliability to wrap the femur defect.…”
Section: Figmentioning
confidence: 99%